TEACHING POSTMODERN AND NARRATIVE SOCIAL WORK PRACTICE THROUGH THE USE OF FILM-BASED CLIENTS - Brown, Catrina (Canadian Social Work Review / Revue canadienne de service social, 2019)
This paper elaborates on the use of film-based clients in teaching narrative therapy in social work. In this paper, I provide my rationale for the use of film-based clients and then highlight the life story of Lars, taken from the film Lars and the Real Girl (2007), as an example of how film clients can be a helpful way of learning how to practice narrative therapy. The theory and epistemology of narrative therapy—and specifically a postmodern approach to the central organizing concepts of story, experience, self, knowledge, and power—are discussed. I then illustrate key elements of narrative practice with Lars as a film-based client. The attention to creating counternarratives challenges dominant social discourses in Lars’ story about mental health and coping with difficult life events, and the internalization of these ideas as part of the story of his identity. A positioned approach against the medicalization and pathologization of Lars’ struggles reflects the social justice commitment of narrative practice.